“Double”, mixed or twin monasteries? The status of so-called “double” monasteries in Byzantium of 8th–15th centuries - Anna Vankova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Already in the early Byzantine Empire (4th–6th centuries), beside monasteries and convents, there were certain kinds of co-existence of monastic communities for men and women, i.e. double, mixed and twin-monasteries. These institutions were inherited by the middle and late Byzantine Empire. The aim of this article is to analyse the evidence of the primary sources and to understand what was concealed under the term dipla monasteria, to see if it was equivalent to the modern scholarly concept of “double monasteries” and to introduce the concept of “twin monasteries”. The article also raises the question about the eff ectiveness of measures taken by patriarch Nikephoros I against joint communities of men and women. It analyses the character of communities in the period after Nikephoros. The study draws on a broad range of sources, namely Justinian’s laws, canons of church councils, hagiographic texts, typica. Following the analysis of the sources, the article comes to the conclusion that διπλ¢ μοναστήρια of canons implied mixed monasteries. However, there were a whole range of other variants of co-existence of men and women in a monastic community. The sources contain information about double monasteries and twin monasteries. These were most common in the fi rst period of the iconoclastic movement, but, on the whole, other types of monasticism prevailed. The measures taken by patriarch Nikephoros did not totally eliminate “double” monasteries.